Carbon TEM grids fabricated using C-MEMS as the platform for suspended carbon nanowire characterization. (March 2017) - Pramanick, Bidhan; Salazar, Arnoldo; Martinez-Chapa, Sergio O.; Madou, Marc J.
Abstract: Carbon transmission electron microscope (TEM) grids were fabricated for the first time using Carbon-MEMS (C-MEMS) process. The C-MEMS process and its application in the fabrication of carbon TEM grids are detailed. The benefits of making carbon TEM grids this way are also explained. Commercially available TEM grids are often hard to use for many types of samples. Moreover sample preparation such as nanowire placement on conventional TEM grids remains very challenging. Here we demonstrate a novel fabrication method of carbon TEM grids. These grids serve as a support for the nanowire deposition process itself; no further nanowire placement is required. The method for constructing in-situ carbon TEM grids is illustrated for the study of suspended carbon nanowires. The method is generic as long as the nano-devices that are being built can survive the pyrolysis step. In this paper, a test-bed for CNW TEM study is fabricated using one step photolithography to pattern SU8 TEM grids and then fibers are electrospun over the grid. Both, grids and fibers are then converted to carbon at the same time by pyrolysis in an inert (N2 ) environment. The grids are made on a Si/SiO2 substrate and are released from the substrate using Buffered Oxide Etch. Graphical abstract: